Risks of Occupational Health: From «inadequate» Management Style to Transformation of Teacher’s Professional Self-Attitude - Dziuba, Tetyana (Psychological Prospects Journal, 2017)
The paper represents the results of empirical study of risks of occupational health, particularly peculiarities of transformation of pedagogue’s professional self-attitude under the influence of «inadequate» management style. The basic definitions of studied problem are determined: occupational health, risks of occupational health, professional self-attitude and «inadequate» management style. Special attention was paid to the fact that destructive characteristics of professional self-attitude (inadequate self-estimation and negative estimation of own work by pedagogue) are formed under the influence of different professional environment factors. «Inadequate» management style is considered as one of the factors transformationofprofessional self-attitude, that significantly influences pedagogue’s occupational health. The results of empirical study of peculiarities relationships between the factor «inadequate» management style (author’s questionnaire «Risks of occupational health» is used) and the indicators of professional self-attitude (K. V. Karpinskyi, O. M. Kolyshko method) are presented and commented. Significant patterns of direct and indirect correlation relationships by such indicators are analyzed: integrative scale «self-effectiveness in profession», which includes scales «self-management in profession» and «self-estimation of personal growth in profession»; «internal proneness to conflict in personal growth in profession»; «self-depreciation in profession». Conclusion that influence of «inadequate» management style on the pedagogue’s professional self-attitude has a number of significant dangerous features for his/her occupational health is made: it rises anxiety, sensitivity of employee; destroys the employee’s hope on the good attitude to him/her and to successes in professional career growth; is projected in negative, distrustful or unkindly attitude to other subjects of professional activity.
Keywords: occupational health, risks of occupational health, professional self-attitude, «inadequate» management style.